Rapidly Evolving Coronary Aneurysm in a Patient with Rheumatoid Arthritis - Reji Pappy; Siddharth Wayangankar; Thomachan Kalapura; Mazen S. Abu-Fadel (Cardiology Research and Practice)
Coronary artery aneurysm (CAA) formation in the setting of an acute inflammatory state due to connective tissue disease is rare. We report a case of rapid progression from an ectatic to an aneursymatic left circumflex coronary artery leading to an acute coronary event in a patient with rheumatoid arthritis (RA). We report the accelerated growth of the aneurysm as it was temporally related to the lapse in treatment and the management strategies involved with this entity.